A tacit knowledge sharing model to enhance stakeholder engagement in requirements elicitation / Law Foong Li - Law , Foong Li (2019)
Elicitation is an activity that uncovers, acquires, and elaborates requirements for a software system from sources such as stakeholders, documents, systems, and others. Inevitably, missing or mistaken requirements often tend to be problematic in requirements elicitation of requirements engineering. One of the reasons is that crucial information such as business rules, goals, expectations or assumptions often remain tacit, hidden or unshared. Most studies strive to expose tacit knowledge during requirements elicitation by developing various techniques which are not universally applied. However, the issue of tacit knowledge in requirements elicitation continues to hinder the quality of the requirements attained. Consequently, it is critical to emphasize the individual characteristics of stakeholders as primary sources of requirements elicitation. This, however, can only be achieved through gaining insight into the personal factors (i.e., personal ability, relevance, and attitude) and psychological factors such as motivation and communication skills of stakeholders. These will reveal the true reason(s) behind the intention of stakeholders to share tacit knowledge, and thus more accurate and complete requirements can be obtained. There are a few studies on proposed tacit knowledge sharing models in software engineering. Regrettably, studies on relationships between the intention to share tacit knowledge and the affecting factors are still very much unexplored in the field. Hence, the purpose of this study is to provide a deeper understanding of the phenomenon. It investigates how personal factors of stakeholders influence the intention of tacit knowledge sharing. Moreover, this study aims to investigate the effect of factors (i.e., motivation and communication skills) relevant to tacit knowledge sharing. The study employs a quantitative research design where data are predominantly gathered through an online questionnaire-based survey, comprising a set of items designed to investigate the perception of software practitioners towards how personal factors influence the intention of stakeholders to share tacit knowledge. It specifically examines the relationship between personal factors and the intention of stakeholders, and the mediating effects of motivation and communication skills on the relationship between the two, predominantly tacit knowledge during requirements elicitation. It has attracted a sample of 320 responses from practitioners in the software industry. The results of the survey are indicated in the proposed model, Tacit Knowledge Sharing (TaKS). TaKS illustrates that personal factors are of primary importance and have significant effects on galvanizing the intention of stakeholders to share tacit knowledge, which is crucial in discovering complete software requirements via the inclusion of mediator variables, namely motivation and communication skills in this study. At last, a prototype is built to validate a part of the proposed research model. This study has provided new empirical findings of the impacts of factors including personal factors, motivation, and communication skills on tacit knowledge sharing intentions, which prior research has neglected. Accordingly, greater focus should be placed on the stakeholders particularly on the personal or intrinsic aspect as stakeholders are the primary source of requirements. This insight can be utilized in practice to better support requirements elicitation to achieve a better quality of requirements in terms of completeness and correctness.